Does diet or macronutrients intake drive the structure and function of gut microbiota? - Li, Yuhang; Yan, Yujie; Fu, Hengguang; Jin, Shiyu; He, Shujun; Wang, Zi; Dong, Guixin; Li, Baoguo; Guo, Songtao (Frontiers in Microbiology, 2023)
Shift of ingestive behavior is an important strategy for animals to adapt to change of the environment. We knew that shifts in animal dietary habits lead to changes in the structure of the gut microbiota, but we are not sure about if changes in the composition and function of the gut microbiota respond to changes in the nutrient intake or food items. To investigate how animal feeding strategies affect nutrient intakes and which thus alter the composition and digestion function of gut microbiota, we selected a group of wild primate group for study. We quantified their diet and macronutrients intake in four seasons of a year, and instant fecal samples were analyzed by high-throughput sequencing of 16S rRNA and metagenomics. These results demonstrated that the main reason that cause seasonal shifts of gut microbiota is the macronutrient variation induced by seasonal dietary differences. Gut microbes can help to compensate for insufficient macronutrients intake of the host through microbial metabolic functions. This study contributes to a deeper understanding of the causes of seasonal variation in host-microbial variation in wild primates.